Mardiyah, S. U. K.., Setyawan, H.., García-Jiménez, J. V.., Eken, Özgür, Latino, F., Pranoto, N. W., Darmawan, A.., Shidiq, A. A. P.., Rahmatullah, M. I., Tafuri, F.., & Anam, K.. (2024). Differences in the Implementation of Physical Education (PE) Learning Management Based on Years of Work: Analysis of Differences in the Quality of Quality Assurance Culture. Retos, 55, 797–803. https://doi.org/10.47197/retos.v55.104865 - Retraction Retraction
Mardiyah, S. U. K.., Setyawan, H.., García-Jiménez, J. V.., Eken, Özgür, Latino, F., Pranoto, N. W., Darmawan, A.., Shidiq, A. A. P.., Rahmatullah, M. I., Tafuri, F.., & Anam, K.. (2024). Differences in the Implementation of Physical Education (PE) Learning Management Based on Years of Work: Analysis of Differences in the Quality of Quality Assurance Culture. Retos, 55, 797–803. https://doi.org/10.47197/retos.v55.104865